Archives & information in the early modern world - Corens, Liesbeth 1988-; Peters, Kate; Walsham, Alexandra 1966-; British Academy; Transforming Information: Record Keeping in the Early Modern World (Conference) (Proceedings of the British Academy, 2018)
Foreword /Eric Ketelaar --Introduction: Archives and information in the early modern world /Alexandra Walsham, Kate Peters, & Liesbeth Corens --Part I: Organization and agency.2.Early modern European archivality: organised records, information, and state power, c. 1500 /Randolph C. Head --3.Archival intelligence: diplomatic correspondence, information overload, and information management in Italy, 1450-1650 /Filippo De Vivo --4.Jean-Baptiste Colbert, accounting, and the genesis of the state archive in early modern France /Jacob Soll --Part II: Access and secrecy.5.The early modern secretary and the early modern archive /Arnold Hunt --6.Knowledge, oblivion, and concealment in early modern Spain: the ambiguous agenda of the Archive of Simancas /Arndt Brendecke --7.'Friction in the archives': access and the politics of record-keeping in revolutionary England /Kate Peters --Part III: Media and materiality.8.The material culture of record-keeping in early modern England /Heather Wolfe & Peter Stallybrass --9.Archiving the archive: scribal and material culture in 17th-century Zurich /Sundar Henny --Part IV: Documentation and distance.10.Truth and suffering in the Quaker Archives /Brooke Sylvia Palmieri --11.Death, distance, and bureaucracy: an archival story /Sylvia Sellers-García --12.The transnational archive of the sinosphere: the early modern East Asian information order /Kiri Paramore --Afterword /Ann Blair.